PP.09.07: THE NECESSITY OF ADRENAL VENOUS SAMPLING IN ALDOSTERONISM PATIENTS YOUNGER THAN AGE 45. (June 2015) - Zhu, L.; Zhang, Y.; Lu, X.; Zhang, J.; Lin, B.; Chu, S.; Wang, Y.; Gao, P.; Zhu, D.; Wang, J.
Abstract : Objective: Background: Adrenal venous sampling (AVS) is an invasive and cost procedure, not all the medical centers can perform it. Considering the prevalence of incidentalomas increases with age, current primary aldosteronism (PA) diagnosis and treatment guideline and the AVS expert consensus both recommended that PA patients younger than age 40 are not necessary to have AVS before adrenalectomy if they have a typical PA profile and a clear unilateral adrenal adenoma on CT scan. To study the necessity of AVS in PA patients younger than age 45. Design and method: This is a retrospective study. 106 patients younger than age 45 who were diagnosed PA in the Department of Hypertension in Ruijin Hospital between 2006 and 2014 were analyzed. PA was confirmed either by fludrocortisone test or saline infusion test. Patients received unilateral adrenalectomy guided by AVS result or by the typical adenoma appearance on adrenal CT image. They were followed after surgery. Group 1 included 39 patients who received successful lateralized AVS. Group 2 had 67 patients including 53 without AVS, 10 with nonlateralized AVS and 4 with unsuccessful AVS. Results: The baseline clinical characters, including age, gender, hypertension duration, 24 hour systolic and diastolic blood pressure, hypokalemia history, the number of antihypertensive medications and the length of follow-up after surgery were not different, respectively, between two groups. Group 2 had significantly higher standing plasma aldosterone and urinary aldosterone level than that of group 1(298.71 ± 153.71 vs 399.67 ± 269.06 (pg/ml), 23.45 ± 14.61 vs 31.52 ± 21.16 ug/24hour, respectively, all P < 0.05), but there were no difference considering plasma renin activity and renin to aldosterone ratio. The adenoma diameter measured from adrenal CT image was different between two groups (1.2 ± 0.72 cm vs 1.5 ± 0.74 cm, P < 0.05). 59% patients in group 1 and 62.7% patients in group 2 had PA cured respectively after surgery (P > 0.05). Conclusions: In this small retrospective study, PA patients younger than age 45 had similar adrenalectomy outcome no matter they received AVS or not. It is suggested therefore that AVS might not be necessary in typical PA patients younger than 45.